Clinical Relevance of Pharmacogenetics in Serotonin Syndrome - Pandya, Dehuti; Tran, My; Verduzco-Gutierrez, Monica (Case Reports in Psychiatry, 2020)
Serotonin syndrome is a predictable life-threatening condition that is caused by serotonergic stimulation of the central and peripheral nervous systems. A patient’s genetic profile can amplify exposure risk as many serotonergic drugs are metabolized by CYP450 enzymes, and these enzymes may be altered in functionality. We report a case of an elderly man who presented with serotonin syndrome after a dose change in valproic acid 5 weeks prior. His medication list consisted of low-dose serotonergic agents, which is unusual as most cases of serotonin syndrome involve higher doses. A review of his pharmacogenetic profile is presented to retrospectively evaluate the additive risk for serotonin syndrome and implications on resuming serotonergic agents.